A new factor in UK students' university attainment: the relative age effect reversal?. Issue 3 (6th July 2015) - Roberts, Simon J.; Stott, Tim
Abstract : Purpose: – The purpose of this paper is to study relative age effects (RAEs) in a selected sample of university students. The majority of education systems across the globe adopt age-related cut-off points for eligibility. This strategy has received criticism for (dis)advantaging those older children born closer to the "cut-off" date for entry into an academic year and for promoting the existence of RAEs. To date, there are only two studies which have examined the relative age phenomenon in a university setting specifically. Design/methodology/approach: – Data of student records from the years 2006-2009 were analysed. Specifically this included date of birth, The Universities and Colleges Admissions Service (UCAS) entry points, gender, grade point averages and final year degree classification. Findings: – Analysis of data collected from 460 university students revealed a significant RAE reversal. Specifically, relatively younger students achieved significantly higher first-class honours degrees than relatively older students ( p < 0.01). Research limitations/implications: – Limitations include the following: the sample was modest and restricted to only 460 students located within one of the universities five faculties. Recent RAE studies in education have recruited thousands of students; therefore, these findings may not be totally representative of the broader UK university population. Originality/value: – This is only the second UK-based study to examine RAEs from a university perspective. The findings highlight an interesting and new insight into the RAE phenomenon and one that warrants further scientific attention.